Pricing and investments in matching markets - George J. Mailath; Larry Samuelson; Andrew Postlewaite (Theoretical Economics, 2013)
Different markets are cleared by different types of prices—seller-specific prices that are uniform across buyers in some markets, and personalized prices tailored to the buyer in others. We examine a setting in which buyers and sellers make investments before matching in a competitive market. We introduce the notion of premuneration values—the values to the transacting agents prior to any transfers— created by a buyer-seller match. Personalized price equilibrium outcomes are independent of premuneration values and exhibit inefficiencies only in the event of “coordination failures,” while uniform-price equilibria depend on premuneration values and in general feature inefficient investments even without coordination failures. There is thus a trade-off between the costs of personalizing prices and the inefficient investments under uniform prices. We characterize the premuneration values under which uniform-price equilibria similarly exhibit inefficiencies only in the event of coordination failures.
Keywords: C78; D40; D41; D50; D83; 330; Directed search; matching; premuneration value; prematch investments; search